Predictors of pulmonary involvement in children with COVID‐19: How strongly associated is viral load?. Issue 1 (30th September 2022) - Yakut, Nurhayat; Yakut, Kahraman; Sarihan, Zeynep; Kabasakal, Irem; Aydin, Murat; Karabulut, Nuran
Abstract: The purpose of this study was to identify risk factors for pulmonary involvement by examining the demographic, clinical, and laboratory characteristics of children with COVID‐19. We performed a retrospective single‐center study of COVID‐19 in children treated at a tertiary care hospital in Turkey from December 2020 to June 2021. During the course of the study, 126 patients were evaluated, of whom 70/126 were male. The patients' ages ranged from 1 to 216 (mean, 4.73 ± 81.11) months. Fever (65.9%), cough (52.4%), and shortness of breath (18.3%) were the most common symptoms of COVID‐19. Ten patients required noninvasive mechanical ventilation. Sixty‐nine patients (54.8%) had pneumonia. Longer duration of fever, hospitalization, and the presence of cough were significantly associated with pulmonary involvement. Children with pneumonia had significantly higher levels of C‐reactive protein (CRP), procalcitonin, erythrocyte sedimentation rate (ESR), and viral load, and significantly lower counts of lymphocytes and thrombocytes. The cutoff viral load, CRP, and procalcitonin values for predicting pulmonary involvement were 26.5 cycle threshold (Ct; 95% confidence interval [CI], 0.54–0.74; sensitivity, 0.65; specificity, 0.56; area under curve [AUC]: 0.647, p  = 0.005), 7.85 mg/L (95% CI, 0.56–0.75; sensitivity, 0.66; specificity, 0.64; AUC = 0.656; p  = 0.003) and 0.105 ng/ml (95% CI, 0.52–0.72; sensitivity, 0.55; specificity, 0.58; AUC = 0.626; p  = 0.02), respectively. High CRP, procalcitonin levels, ESR, and viral load, and low lymphocyte and thrombocyte counts can predict pulmonary involvement in children with COVID‐19, so better management may be provided for good prognosis.